Associations of Dietary Intakes of Total and Specific Types of Fat with Blood Lipid Levels in the Filipino Women's Diet and Health Study (FiLWHEL) - Heejin Lee; Hyojin Kim; Sherlyn Mae P. Provido; Minji Kang; Grace H. Chung; Jae W. Lee; Sangmo Hong; Sung Hoon Yu; Chang Beom Lee; Jung Eun Lee (Ubiquity Press, 2023)
Background: Limited evidence exists on the association between dietary fat intake and lipid profiles in Southeast Asian populations. Objectives: We aimed to examine the cross-sectional associations of dietary intake of total and specific types of fat with dyslipidemia in Filipino immigrant women in Korea. Methods: We included 406 Filipino women married to Korean in the Filipino Women's Diet and Health Study (FiLWHEL). Dietary fat intake was assessed using 24-hour recalls. Impaired blood lipid profiles were defined as high total cholesterol (TC) (≥200 mg/dL), high triglyceride (TG) (≥150 mg/dL), high LDL Cholesterol (LDL-C) (≥ 130 mg/dL), or low HDL cholesterol (HDL-C) (<50 mg/dL). The genomic DNA samples were genotyped using DNA chip. The odds ratios (ORs) and 95% confidence intervals (CIs) were calculated using multivariate logistic regression. Results: Substituting carbohydrates with dietary saturated fat (SFA) intake was associated with increased prevalence of dyslipidemia; ORs (95% CIs) for subsequent tertiles compared to the first tertile were 2.28 (1.19-4.35), and 2.88 (1.29-6.39) (P for trend = 0.02). When we examined individual markers, ORs (95% CIs, P for trend) comparing the third to the first tertile were 3.62 (1.53-8.55, 0.01) for high TC, 1.46 (0.42-5.10, 0.72) for high TG, 4.00 (1.48-10.79, 0.02) for high LDL-C, and 0.69 (0.30-1.59, 0.36) for low HDL-C. When we examined the interaction by LDL-C-related polymorphisms, the association with dyslipidemia was more pronounced among participants with CC alleles than among those with T alleles of rs6102059 (P for interaction = 0.01). Conclusions: High dietary SFA intake was significantly associated with a high prevalence of dyslipidemia in Filipino women in Korea. Further prospective cohort studies are warranted to determine risk factors for CVD in Southeast Asian populations.